Life Testing of Ni-YSZ Fuel Electrodes under Electrolysis, Fuel Cell, and Current Switching Operation. (30th May 2017) - Liu, Qinyuan; Wang, Hongqian; Kennouche, David; Riscoe, Casey; Butts, Danielle; Barnett, Scott A
Abstract : An electrode supported Ni-YSZ/YSZ/Ni-YSZ symmetric cell was studied in life tests with constant current and switching current operation. At a current density of 0.2 A/cm 2, there was no evidence of degradation. The cell electrochemical performance degraded slightly during life tests at current densities ≥ 0.8 A/cm 2, with the ohmic resistance increasing and polarization resistance decreasing. The electrode/electrolyte interface structure was found to be seriously degraded after the life tests, with the formation of interfacial voids. In addition, grain boundary voids were observed within the YSZ electrolyte, especially after constant current operation. These observations presumably explain the observed electrolyte resistance increase. Both Ni and YSZ nanoparticles were observed in the electrode functional layers after life tests, possibly explaining the decrease of polarization resistance.